Modeling a Large Coastal Upwelling Event in Lake Superior. Issue 5 (30th April 2021) - Li, Yaru; Beletsky, Dmitry; Wang, Jia; Austin, Jay; Kessler, James; Fujisaki‐Manome, Ayumi; Bai, Peng
Abstract: An extraordinary strong wind‐driven upwelling event occurred in Lake Superior in summer of 2010 when the lake was strongly stratified. In this paper, a detailed three‐dimensional (3‐D) investigation of the current and thermal structures during the upwelling event was conducted using in situ observations, remote sensing products, and the results of a long‐term numerical simulation. A 3‐D finite‐volume coupled ice–ocean model tailored for the Laurentian Great Lakes was employed for this purpose. The model was validated with temperature observations at National Oceanic and Atmospheric Administration buoys and mooring data from 2010. The upwelling event observed in satellite imagery and at a mooring station was reproduced by the model, showing a cooling of as much as 10°C in August 2010 along the northwestern coast. The relationship between the alongshore wind and the offshore thermocline displacement (upwelling front) derived in theoretical work (Csanady, 1977, https://doi.org/10.1029/JC082i003p00397 ) was used to calculate upwelling front movement offshore and found to be in in close agreement with model prediction. A significant correlation between alongshore wind stress and lake temperature change in the upwelling zone was found with a correlation coefficient of −0.87. A simple linear heat balance model explained most of variability in temperature. Plain Language Summary: An extraordinary strong upwelling event observed during summer 2010 in Lake Superior was reproduced by a numerical ocean model. A detailed three‐dimensional (3‐D) investigation of the current and thermal structures during the upwelling event was conducted using in situ observations, remote sensing products, and the results of a long‐term numerical simulation. A 4‐day long strong, persistent alongshore wind was the major driving force of this event. A significant correlation between alongshore wind stress and lake temperature change in the upwelling zone was found. A simple linear heat balance model explained most of variability in temperature measurements. The relationship between the alongshore wind and the offshore displacement of the upwelling front derived in theoretical work was used to calculate upwelling front movement offshore and found to be in in close agreement with model prediction. Key Points: An extraordinarily strong upwelling event observed during summer 2010 in Lake Superior was reproduced by a coupled ice–ocean model Strong correlation between lake surface temperature change in the upwelling zone and alongshore wind stress was found (with a correlation coefficient of −0.87); a simple linear heat balance model explained most of time rate of change in temperature Offshore thermocline displacement (upwelling front) in the model was in good agreement with predictions of an analytical model that employed alongshore wind and initial thermal structure